Jihad Intelektual Generasi Milenial: Muqobalah QS. At Taubah Ayat 122 dan Pesan Perdamaian dalam Syair Al Jihad Wal-Ijtihad Karya KH. Saaduddin Annasih, Lc., M.Pd - Ustadzi, Aan Heri (JURNAL AT-TURAS, 2020)
This article explains the command to deepen (intellectual) knowledge in verse QS. At Taubah Verse 122 will muqobalah with SyairJihad Wal-Ijtihad. they are millennials who will replace the ulemas and national leaders and explain the values of the current peace of jihad contained in the Poem Al-jihad Wal-Ijtihad by KH. Saaduddin Annasih, Lc., M.Pd, said that jihad in the colonial era and jihad today cannot be equated because the context is not jihad using spiked bamboo, spear, arrow, wooden stone, etc. but in today's jihad, namely intellectual jihad. Where the millennial era generation must be able to read the era, respond to the age, and solve the problems that often arise in this melineal era carefully. So that this millennial generation must have a responsive, solutive attitude.Keywords: Jihad, Intellectual, Millennial, and Peace.